ANALISIS PENGGUNAAN RADAR UNTUK MENUNJANG KESELAMATAN PELAYARAN DI MT. NEW WINNER - Muhammad Farhan; Rizal Rochmansyah; Achmad Ali Mashartanto (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Radar plays a crucial role in detecting objects around a ship, determining the distance and direction of targets, and assisting decision-making to avoid navigational hazards and the risk of collision. This study aims to analyze the use of radar to support navigational safety on MT. New Winner. The research method used was qualitative with a descriptive approach. Data were obtained through direct observation during sea practice on MT. New Winner, interviews with navigational officers, documentation related to radar operating procedures (SOPs), and fishbone data analysis. The results indicate that radar use on MT. New Winner was implemented in accordance with the company's standard operating procedures (SOPs). However, several factors can still interfere with radar performance, including human factors (lack of continuous supervision), mechanical factors (radar component interference), method factors (inappropriate gain and clutter settings), and natural factors such as heavy rain and high waves.Efforts to overcome these disturbances include improving officers’ competence through training and equipment familiarization, conducting routine maintenance and inspections of radar equipment, consistently applying SOP, and adjusting radar settings according to weather and navigational conditions. By optimizing radar usage and enhancing operator understanding, navigational safety on board MT. New Winner can be better ensured and the risk of maritime accidents can be minimized.